MASS ETHNIC ART AND SOCIAL LIFE: जन जातीय रंग कला एवं सामाजिक जीवन - Jain, Nisha (International Journal of Research -GRANTHAALAYAH, 2014)
Tribal societies are of a different nature than civilized and developed societies. They have their own specific culture. Each tribe’s own culture makes them different from other tribes. Traditionally inherited culture is the basis of his life. Due to this particular culture, they fulfill many of their needs. Tribal art is reflected in various social celebrations and rituals. The members of each tribe celebrate the joys of life through art and color that is reflected in their traditional clothes, colorful jewelery and adornment. They do not need any training for this art, their knowledge is automatically gained from generation to generation. जनजातीय समाज सभ्य एवं विकसित समाज की तुलना में भिन्न प्रकृति के होते हैं। उनकी अपनी विषिष्ट संस्कृति होती है। प्रत्येक जनजाति को स्वयं की संस्कृति उन्हें दूसरी जनजातियों से भिन्न बनाती है। परम्परागत रूप से विरासत में प्राप्त हुई संस्कृति उनके जीवन का आधार है। इस विषिष्ट संस्कृति कें कारण वे अपनी बहुत सी आवष्यकताएं पूर्ण करते हैं। विभिन्न सामाजिक उत्सवों रीति रिवाजों में जनजातीय कला की झलक दिखलाई देती है।प्रत्येक जनजाती के सदस्य कला एवं रंगों के माध्यम से जीवन की खुषियां मनाते हैं जो उनके परम्परागत वस्त्रों, रंग बिरंगे आभूषणों एवं श्रृंगार से दिखलाई देता है। इस कला के लिए उन्हें किसी प्रषिक्षण की आवष्यकता नहीं होती है इसका ज्ञान उन्हें स्वतः पीढ़ी दर पीढ़ी प्राप्त होता चला जाता है।